Development of stratified spruce-birch stands in Latvia - Dudelis, Janis (SLU/Southern Swedish Forest Research Centre, 2013)
Natural properties of Norway spruce (Picea abies) and birch (Betula spp.)suggest a good ecological ability to form a stratified mixture with birch in a upper and spruce in a lower stratum. Maintaining birch as the shelter over planted spruce in the beginning of rotation might result in higher overall yield than spruce monocultures. Other advantages such as higher ecological stability, increased biodiversity and better economic performance have been demonstrated by studies in other Northern European countries.